On the Nonlinear Instability of Traveling Waves for a Sixth-Order Parabolic Equation - Zhenbang Li; Changchun Liu (Abstract and Applied Analysis)
We study the instability of the traveling waves of a sixth-order parabolic equation which arises naturally as a continuum model for the formation of quantum dots and their faceting. We prove that some traveling wave solutions are nonlinear unstable under 𝐻4 perturbations. These traveling wave solutions converge to a constant as 𝑥→∞.